Stability Study of Isoniazid and Rifampicin Oral Solutions Using Hydroxypropyl-Β-Cyclodextrin to Treat Tuberculosis in Paediatrics - Ana Santoveña-Estévez; Javier Suárez-González; Amor R. Cáceres-Pérez; Zuleima Ruiz-Noda; Sara Machado-Rodríguez; Magdalena Echezarreta; Mabel Soriano; José B. Fariña (MDPI AG, 2020)
(1) Background: First-line antituberculosis treatment in paediatrics entails the administration of Isoniazid, Pyrazinamide, and Rifampicin. This study examines the possibility of developing a combined dose liquid formulation for oral use that would facilitate dose adjustment and adherence to treatment for younger children. (2) Methods: The active pharmaceutical ingredients stability under in vitro paediatric digestive pH conditions have been checked. The samples were studied as individual or fixed combined paediatric dosages to determine the pH of maximum stability. The use of hydroxypropyl-β-cyclodextrin to improve Rifampicin solubility and the use of ascorbic acid to increase the stability of the formulation have been studied. (3) Results: Maximum stability of combined doses was determined at pH 7.4, and maximum complexation at pH 8.0. Taking this into account, formulations presented the minimum dose of two active pharmaceutical ingredients dissolved. The addition of ascorbic acid at 0.1% w/v enables the detection of a higher remaining quantity of both drugs after three days of storage at 5 °C. (4) Conclusions: a formulation which combines the minimum paediatric dosages dissolved recommended by WHO for Isoniazid and Rifampicin has been developed. Future assays are needed to prolong the stability of the formulation with the aim of incorporating Pyrazinamide to the solution.